Pengaruh Konten Digital Marketing di Tiktok dan Instagram terhadap Minat Beli Konsumen - Maulana, Sarip; Puji Isyanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of social media has driven significant changes in digital marketing strategies, particularly through the TikTok and Instagram platforms. This study aims to determine the influence of digital marketing content displayed on these two platforms on consumer purchasing interest. This study employs a quantitative approach using a causal-comparative method. Data was collected through an online questionnaire distributed to 30 respondents who are active users of TikTok and Instagram aged 17–35 years. The research instrument was designed using a 1–5 Likert scale and analyzed using multiple linear regression techniques with the assistance of SPSS version 25. The results indicate that digital marketing content on TikTok (X1) has a positive and significant influence on consumer purchasing interest with a significance value of 0.016 < 0.05. Meanwhile, digital marketing content on Instagram (X2) shows a positive but insignificant influence on consumer purchasing interest, with a significance value of 0.538 > 0.05. The simultaneous test indicates that both independent variables together have a significant effect on the dependent variable, with an F sig value < 0.05 and a coefficient of determination (Adjusted R²) value of 59.10%. These results indicate that TikTok has a stronger influence than Instagram in affecting consumer purchase intent, particularly among the younger age group that dominates active users of both platforms. This study provides insights for businesses to optimize their digital marketing strategies based on short, interactive videos on social media.